A DNA Vaccine Against Proadrenomedullin N-Terminal 20 Peptide (PAMP) Reduces Angiogenesis and Increases Lymphocyte and Macrophage Infiltration but Has No Effect on Tumor Burden in a Mouse Model of Lung Metastasis - Tom Kalathil Raju; Srdan Tadic; Pablo Garrido; Laura Ochoa-Callejero; Judit Narro-Íñiguez; Josune García-Sanmartín; Alfredo Martínez (Vaccines)
Background/Objectives: Nucleic acid-based anticancer vaccines are becoming a very active field in the fight against cancer. Here, our goal was to generate an oral DNA vaccine targeting the angiogenic peptide, proadrenomedullin N-terminal 20 peptide (PAMP). Methods: An expression plasmid (PcPAMP) was generated by fusing the tetanus toxin epitopes P2 and P30 to the mouse PAMP sequence to counteract self-tolerance, and the empty plasmid was used as a negative control (PcNeg). The plasmids were introduced into Salmonella typhimurium bacteria that were then transformed into bacterial ghosts. C57BL/6J mice were orally immunized with the ghosts five times at 2-week intervals. Then, B16-F10 melanoma cells were injected into the tail vein to generate lung metastases. Furthermore, naïve CD4+ T cells were exposed to PAMP, and their secretome was analyzed by proximity extension assays. Results: Significant levels of anti-PAMP immunoglobulins were detected in the blood of PcPAMP-vaccinated mice and their levels of spleen CD8+ T cells were significantly higher than in those treated with PcNeg, indicating that self-tolerance was effectively broken. Although the number and size of lung metastases was similar between both experimental groups, there was a significant reduction in intratumoral angiogenesis and in cancer cell proliferation index in the PcPAMP group. Furthermore, these animals showed an intense infiltration of lymphocytes, including regulatory T cells, and M2-like macrophages into the metastases, that was not evident in the PcNeg group. In addition, PAMP induced upregulation of IL1β, IL6, IL7, IL12, IL27, TNFα, and FGF21, and downregulation of IL16 in naïve CD4+ T cells. Conclusions: Although the vaccine was not effective in reducing tumor growth, new proliferative and immune functions have been described for PAMP. These new functions include induction of melanoma proliferation and modulation of lymphocyte and macrophage tumor infiltration dynamics.